Cost Benefit Analysis of Animal Husbandry in Gajuri Rural Municipality, Dhading - Basnet, Vidya Darshan; Bista, Raghu Bir (Janabhawana Research Journal, 2025)
Animal husbandry serves as a primary source of income and employment. However, there is limited information on the actual costs and benefits households incur from this practice. This study aimed to estimate the cost-benefit structure of dairy cattle farming and examine the socioeconomic factors influencing herd size in Gajuri Rural Municipality. Data were collected from 196 livestock-keeping households across 8 wards using a census method and structured questionnaires. Descriptive statistics, charts, and graphs were employed to present cost and benefit insights, while Ordinary Least Squares method identified the determinants of herd size. The findings revealed that at local price, the net benefit was Rs. -119,657.1 including labor cost and Rs. 73,643.9 excluding it, resulting in a benefit-cost ratio (B/C) of 0.59 and 1.75, respectively. At market price, net benefits were Rs. 23,885.9 including labor and Rs. 217,187.0 excluding labor, with B/C ratios of 1.08 and 3.21, respectively. These outcomes suggest that dairy cattle farming can be economically beneficial, especially when household labor is not monetarily accounted for and market prices are considered. Additionally, ethnicity, landholding size, and remittance income were found to significantly influence herd size, underlining key socioeconomic determinants in livestock investment decisions.